Antioxidant supplementation of cryopreservation extenders improves post-thaw sperm viability in the red-crowned toadlet, Pseudophryne australis - Howard, Morgan S.; Byrne, Phillip G.; O’Brien, Justine K.; Hobbs, Rebecca J.; Silla, Aimee J. (Frontiers in Amphibian and Reptile Science, 2025)
Amphibians are currently experiencing the highest extinction rate of any vertebrate class. Gamete cryopreservation and the biobanking of genetic resources are important conservation tools to safeguard the genetic diversity of imperiled species. While amphibian oocytes/embryos have proven difficult to cryopreserve, amphibian sperm cryopreservation has been achieved in a growing number of species, though with variable post-thaw recovery. Oxidative stress is a major cause of cell damage during cryopreservation and results in compromised post-thaw sperm quality. Supplementation of cryopreservation extenders with antioxidants has been shown to benefit the post-thaw recovery of sperm from a number of mammal and fish species, however research investigating potential benefits to amphibian sperm cryopreservation is lacking. The aim of the present study was to quantify the effect of antioxidant supplementation (2mM melatonin, 2mM ascorbic acid, 2mM uric acid, or control cryodiluent on sperm viability, motility, and velocity in the near-threatened red-crowned toadlet, Pseudophryne australis. A split-sample experimental design was adopted, whereby single-male sperm suspensions (n = 8) were evenly divided among four experimental treatments (control, melatonin, ascorbic acid, and uric acid). Sperm suspensions were cryopreserved, and post-thaw sperm quality metrics assessed (sperm viability [live/dead], percentage total sperm motility, percentage forward progressive motility [FPM], curvilinear velocity [VCL], and average path velocity [VAP]). Melatonin and uric acid treatments exhibited significantly higher sperm viability compared to the control treatment, with the ascorbic acid treatment exhibiting intermediate mean viability. Motility parameters were not significantly different among treatments, though motility and velocity metrics tended to be higher in the ascorbic acid treatment. Overall, this study provides the first evidence that antioxidant supplementation of cryopreservation extenders can improve post-thaw sperm quality in an amphibian, and paves the way for future research.